1990
DOI: 10.1021/ma00213a006
|View full text |Cite
|
Sign up to set email alerts
|

Poly(aryl ether-benzoxazoles)

Abstract: A general method for the preparation of poly(aryl ether-benzoxazoles) has been developed where the generation of an ether linkage is the polymer-forming reaction. We found that aryl fluorides para to a 2-benzoxazolyl group were activated toward nucleophilic aromatic substitution with phenoxides. Facile displacement occurred at this position since the benzoxazole ring can stabilize the negative charge developed in the transition state through a Meisenheimer complex, analogous to conventional activating groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 5 publications
3
98
0
Order By: Relevance
“…In previous research, Hilborn et al demonstrated oxazole-activated fluoro-displacement as a route to synthesize PBO with aryl ether linkages. [12] The resulting poly(ether benzoxazole) was soluble in NMP even at high solid concentration (15-25 wt.-%). This one step method has been extended here to synthesize processable poly(aryl ether ketonebenzoxazole) (PAEKBO) copolymers with benzoxazolecontaining and ether-ketone-containing segments in the polymer main chains.…”
Section: Structure Of Paekbomentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, Hilborn et al demonstrated oxazole-activated fluoro-displacement as a route to synthesize PBO with aryl ether linkages. [12] The resulting poly(ether benzoxazole) was soluble in NMP even at high solid concentration (15-25 wt.-%). This one step method has been extended here to synthesize processable poly(aryl ether ketonebenzoxazole) (PAEKBO) copolymers with benzoxazolecontaining and ether-ketone-containing segments in the polymer main chains.…”
Section: Structure Of Paekbomentioning
confidence: 99%
“…the distillation of CHP under a vacuum. [12] The long reaction time and high temperature conditions made the reaction procedure complicated. PPA is a relatively common solvent for preparing heterocyclic compounds by a condensation method and the reactions readily proceed at %200 8C.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…4,4Ј-difluorobenzophenone and 4,4Ј-difluorodiphenylsulfone were commercially available compounds. Although 2,2-bis[2-(4-fluorophenyl)benzoxazol-6-yl]hexafluoropropane had been prepared from the condensation reaction of 2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane and 4-fluorobenzoic acid, 18 we found that shorter reaction time (12 h vs. 2-4 days) and lower cyclodehydration temperature (180°vs. 260°C) were needed in the presence of trimethylsilyl polyphosphate.…”
Section: Bis(benzocyclobutene)-terminated Aryl Ether Monomersmentioning
confidence: 67%
“…The electronic effect of an oxadiazole heterocycle on the 2-phenyl group can be evaluated by 1 H NMR, as the deshielding of the proton ortho to a substituent is indicative of an electron-withdrawing group 27,32,33) . The 1 H NMR spectral assignments for monomers 4 a -4 c showed the ortho protons of the 2-phenyl ring (H mers 4 a -4 c and p-cresol were carried out in an NMP or DMAc/toluene solvent mixture in the presence of K 2 CO 3 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%